Analisis Spasial Sifat Fisiko-Kimia Tanah pada Lahan Terdampak Erupsi Marapi di Nagari Lasi Kabupaten Agam - Yulnafatmawita Yulnafatmawita; Adrinal Adrinal; Aprisal Aprisal (Jurnal Solum, 2026)
The physicochemical properties of soil play a crucial role in determining plant growth, development, and productivity. However, these properties are highly dynamic and can change due to management practices as well as natural phenomena such as volcanic eruptions. This study was aimed to analyze the physicochemical properties of soils under several land-use types (forest, coffee, chili, and rice fields) in Nagari Lasi following Marapi eruption on Dec 03, 2023. Undisturbed and disturbed soil samples were collected at depths of 0–30 cm and 30–60 cm. The results showed that, in general, there were no significant differences in either the physical or the chemical properties of soils across land-use types and soil depths. The soil texture in all land uses and depths was classified as sandy–silt loam, with a very low clay content (5–22%). The bulk density (BD) was <0.80 Mg m⁻³, total soil porosity (TSP) was moderate, and the hydraulic conductivity (HC) rate was high (20–31 cm h⁻¹), except in rice fields (5.34 cm h⁻¹). The plasticity index (PI) was low in both soil layers (2.21–5.31% at 0–30 cm and 5.63–7.21% at 30–60 cm). Soil chemical properties were also not significantly different among the land uses, particularly pH (5.12–5.86) and total N (0.13–0.41%) for both depths. However, the C/N ratio in the 0–30 cm layer tended to be lower than that in the 30–60 cm layer.